Comparison of immunofluorescence and immunoperoxidase methods for viral diagnosis at a distance: a WHO collaborative study - Gardner, P. S. (1978)
Nasopharyngeal secretions collected in Newcastle were examined in both Newcastle and Stockholm for the presence of influenza virus type A and respiratory syncytial (RS) virus by immunofluorescence and immunoperoxidase techniques. A total of 139 specimens were examined in this way and the agreement between the two centres for immunofluorescence was 94% for influenza virus A, 95% for respiratory syncytial virus, and 95% for negative specimens. This technique can therefore be used for examining specimens taken at great distances from the collecting laboratory. The results of the immunoperoxidase technique were unsatisfactory mainly because of the presence of endogenous peroxidase. Measures taken to remove this also destroyed RS virus antigen. It is premature to introduce the immunoperoxidase technique for rapid virus diagnosis, but in due course, when the problems outlined in this article are solved, it could become a useful technique.